CEPR2 phosphorylates and accelerates the degradation of PYR/PYLs in Arabidopsis - Yu, Zipeng (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.